2022
DOI: 10.1111/cod.14110
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and obesity are associated with chronic hand eczema and severity of hand eczema: Data from the Dutch general population

Abstract: 2-hydroxyethyl methacrylate, artificial nail modelling systems, case report, dental plastic fillings, occupational contact dermatitis 2-Hydroxyethyl methacrylate (HEMA; CAS No. 868-77-9) is a plastic material used in printing industry, artificial nail modelling systems such as gel nails and long-lasting nail polish, and in dental plastic fillings.HEMA is applied in a viscous monomeric form and cured into a solid polymeric structure with ultraviolet light. HEMA as a monomer is strongly allergenic but is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…Research by Loman et al . 23 found that overweight and obesity BMI may have a positive relationship with the incidence of HE. Obesity and high waist circumference were shown to be related to the incidence of HE.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Research by Loman et al . 23 found that overweight and obesity BMI may have a positive relationship with the incidence of HE. Obesity and high waist circumference were shown to be related to the incidence of HE.…”
Section: Discussionmentioning
confidence: 94%
“…Increased visceral fat can work as an endocrine organ that activates macrophages and releases pro-inflammatory cytokines that can lead to immune dysregulation. 23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations